A PPS composite material and its preparation method and application

By using PPS resins with different melt indexes in PPS materials and adding PPE resin, glass fiber, graphite and carbon nanotubes, the problem of high fluidity and insufficient crystallization of PPS materials during injection molding is solved, and the resistance stability and dimensional stability of the material are achieved.

CN117430951BActive Publication Date: 2025-04-01KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311624101.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-04-01
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Polyphenylene sulfide (PPS) materials have excessive fluidity during injection molding, resulting in flashes and burrs. Due to failure to crystallize sufficiently, the injection molded parts have problems with post-crystallization shrinkage deformation and warping, and internal stress also leads to deformation of the parts during long-term use.

Method used

By combining PPS resins with different melting indexes and adding PPE resin, glass fiber, graphite and carbon nanotubes, the composition and processing technology of the material are optimized to reduce the crystallization and internal stress of the material, and improve resistance stability and dimensional stability.

Benefits of technology

The resistance stability and dimensional stability of PPS composite materials are achieved, the problems of poor flow performance and poor mechanical performance are avoided, and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004580079960000051
    Figure BDA0004580079960000051
  • Figure BDA0004580079960000061
    Figure BDA0004580079960000061
  • Figure BDA0004580079960000071
    Figure BDA0004580079960000071
Patent Text Reader

Abstract

The present disclosure provides a PPS composite material and its preparation method and application, which belongs to the technical field of polyphenylene sulfide materials. The PPS composite material disclosed in the present disclosure improves the resistance stability and dimensional stability of the PPS composite material on the basis of ensuring the mechanical properties of the PPS composite material by compounding PPS resins with different melt indexes; avoids the shortcomings of poor flow performance of low melt index materials and poor mechanical properties of high melt index materials; uses PPE resin as a dispersed phase to improve the fusion of each component and PPS resin, and further improves the resistance stability and dimensional stability of the PPS composite material; through the compounding of graphite and glass fiber, graphite can reduce the anisotropy of glass fiber reinforced PPS, thereby reducing the difference in shrinkage rate in the perpendicular flow direction and the parallel flow direction, inhibiting the warping of the PPS composite material, and improving the dimensional stability of the PPS composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of polyphenylene sulfide materials, and in particular to a PPS composite material and a preparation method and application thereof. Background Art

[0002] Polyphenylene sulfide (PPS) is widely used in aerospace, automotive functional parts and other fields due to its good mechanical properties, self-flammability, excellent fatigue performance and temperature resistance. However, polyphenylene sulfide materials also have obvious disadvantages. During the injection molding process, its fluidity is too high, resulting in flash and burrs on injection molded products, which brings some troubles to the molding process. As a crystalline material, PPS has a very high degree of crystallinity, but the injection molding industry usually pursues high efficiency and cannot achieve the production cycle and process conditions that can fully crystallize PPS. This causes shrinkage deformation and warping problems caused by post-crystallization during the subsequent storage and use of injection molded parts. At the same time, there are also problems of internal stress in injection molded parts, which are common to all polymers. Internal stress can also cause deformation of parts during long-term use.

[0003] Conductive plastics are widely used in electronic appliances, electronic packaging, industrial equipment, and automotive electronics. At the same time, conductive PPS inherits the advantages of PPS resin in excellent heat resistance, high strength, and fatigue resistance, and is widely used in many fields. The pain point of conductive materials is mainly that composite conductive materials are often affected by many factors such as material fluidity, processing technology, and mold structure, and the conductivity is often unstable.

[0004] CN110776742A proposes to increase the anisotropic shrinkage of the material by adding flat glass fibers and glass microspheres, and the effect is good; however, the addition of glass microspheres will further reduce the toughness of the PPS material, limiting the application of the material.

[0005] CN112812562A proposes to reinforce the composite of ground glass fiber and conventional glass fiber and reduce the warping of the material by introducing hollow glass microspheres. However, when the hollow glass microspheres are processed by a twin-screw extruder, the breakage rate of the hollow glass microspheres is difficult to achieve precise control, resulting in large differences in material properties. Summary of the invention

[0006] The purpose of the present disclosure is to overcome the deficiencies of the prior art and to provide a PPS composite material and a preparation method and application thereof, wherein the PPS composite material has excellent resistance stability and dimensional stability.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: to provide a PPS composite material, comprising the following components in parts by weight: 10-40 parts of a first PPS resin, 10-40 parts of a second PPS resin, 10-30 parts of a PPE resin, 10-40 parts of glass fiber, 5-15 parts of graphite, and 0.5-5 parts of carbon nanotubes; wherein the melt index of the first PPS resin at 316°C and 5kg is 200-500g / 10min; the melt index of the second PPS resin at 316°C and 5kg is 1000-2000g / 10min.

[0008] In the present disclosure, the melt index of the PPS resin is tested according to the ISO1133 test standard; wherein the melt index of the first PPS resin at 316°C and 5kg can be, but is not limited to, 200g / 10min, 250g / 10min, 300g / 10min, 350g / 10min, 400g / 10min, 450g / 10min, and 500g / 10min;

[0009] The melt index of the second PPS resin at 316°C and 5kg may be, but is not limited to, 1000 g / 10min, 1100 g / 10min, 1200 g / 10min, 1300 g / 10min, 1400 g / 10min, 1500 g / 10min, 1600 g / 10min, 1700 g / 10min, 1800 g / 10min, 1900 g / 10min, or 2000 g / 10min.

[0010] Furthermore, the weight proportion of the first PPS resin may be, but is not limited to, 10, 15, 20, 25, 30, 35, or 40 parts; the weight proportion of the second PPS resin may be, but is not limited to, 10, 15, 20, 25, 30, 35, or 40 parts.

[0011] In the present application, based on the mass of the PPS composite material as 100%, the total mass of the first PPS resin and the second PPS resin is not less than 20%, preferably not less than 30%; the mass of the PPE resin is not less than 5%, preferably not less than 10%.

[0012] The present invention compounds linear PPS resins with different melt indexes, which can reduce the crystallization and internal stress of the PPS composite material while ensuring the mechanical properties of the PPS composite material, and improve the resistance stability and dimensional stability of the PPS composite material; avoids the shortcomings of poor flow properties of low melt index materials and poor mechanical properties of high melt index materials; and the present invention adds PPE resin to the PPS composite material, uses the PPE resin as a dispersed phase, improves the fusion of each component and the PPS resin, and further improves the resistance stability and dimensional stability of the PPS composite material.

[0013] In this application, graphite and glass fiber are added for compounding. Graphite can reduce the anisotropy of glass fiber reinforced PPS, thereby reducing the difference in shrinkage between the perpendicular flow direction and the parallel flow direction, inhibiting the warping of the PPS composite material, and improving the dimensional stability of the PPS composite material. Adding graphite alone will cause the resistance stability of the PPS composite material to decrease significantly; this application improves the resistance stability of the PPS composite material on the one hand, and on the other hand, improves the dimensional stability of the PPS composite material by compounding graphite and carbon nanotubes.

[0014] In one embodiment, the graphite is flake graphite.

[0015] In one embodiment, the average particle size of the graphite is 10-80 μm; preferably, the average particle size of the graphite is 25-50 μm.

[0016] In the present application, the average particle size of graphite is measured by the following method: a 20 wt% aqueous solution of sodium hexamethylphosphate and a graphite sample are placed in a 100 ml beaker, and then dispersed for 30 minutes using an ultrasonic disperser. The solution is added to the chamber of a laser scattering particle size analyzer (MICROTRAC HRA (Nikkiso Co., Ltd.) 9320-X100), and the volume distribution is measured for a measurement time of 120 seconds. The particle size of 50% of the measured volume distribution is taken as the average particle size.

[0017] The structure and particle size of graphite are key factors affecting the performance of PPS composite materials. Compared with earthy graphite, the flake structure of flake graphite has better lubricity and flexibility, which can better reduce the anisotropy of glass fiber reinforced PPS, inhibit warping, and improve the dimensional stability of PPS composite materials. Among them, the average particle size of graphite can be but not limited to 10μm, 13μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm; preferably 25-50μm, within the above preferred range, the dimensional stability and resistance stability of PPS composite materials can be further improved. Further, the weight of graphite can be but not limited to 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts.

[0018] In one embodiment, the intrinsic viscosity of the PPE is 20-50 cm 3 / g; preferably, the viscosity of the PPE is 20-30cm 3 / g.

[0019] The viscosity of PPE can be but not limited to 20 cm 3 / g, 25cm 3 / g, 28cm 3 / g, 30cm 3 / g, 33cm 3 / g, 35cm 3 / g, 37cm 3 / g, 40cm 3 / g, 42cm 3 / g, 45cm 3 / g, 47cm 3 / g, 50cm 3 / g. Compared with other PPE with viscosity of 20-30cm 3 / g PPE can make the product have lower warpage and better resistance stability.

[0020] In this application, the viscosity of PPE is tested by the following method: weigh (0.250±0.002)g of dried sample, transfer to a 50mL volumetric flask, add 15mL of chloroform, shake to completely dissolve the sample, then dilute to the scale with chloroform at 25°C and shake well. Before the measurement, filter the solution with a glass sand core funnel, rinse the filter device and Ubbelohde viscometer with a small amount of solution, and add the filtered solution to the Ubbelohde viscometer so that the liquid level is between the liquid filling marks. Install the Ubbelohde viscometer in the constant temperature water bath of the Ubbelohde viscometer at (25.0±0.1)°C, ensure that the viscosity tube is vertical, and the upper mark is at least 30mm below the water bath surface. After constant temperature for 15 minutes, measure the flow time of the sample. The intrinsic viscosity of PPE is calculated by the flow time.

[0021] In one embodiment, the weight portion of the glass fiber is 25-35 parts.

[0022] In one embodiment, the weight proportion of carbon nanotubes may be, but is not limited to, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 parts; preferably 1-3 parts of carbon nanotubes.

[0023] In one embodiment, the chopped glass fibers have a diameter of 10-15 μm, a length of 3-6 mm, and are surface treated with polyurethane. Compared with glass fibers surface treated with a silane coupling agent, glass fibers surface treated with polyurethane can improve the compatibility of glass fibers with other components, improve the dispersibility of glass fibers, and thus improve the dimensional stability of the product.

[0024] In the present application, the diameter of the chopped glass fibers is measured using an optical microscope, and the length is measured using a vernier caliper.

[0025] In one embodiment, the ratio of the total mass of the first PPS resin and the second PPS resin to the mass of the PPE resin is (2:1)-(5:1).

[0026] The inventors found that when the ratio of the total mass of the first PPS resin and the second PPS resin to the mass of the PPE resin is (2:1)-(5:1), the resulting PPS composite material has better comprehensive properties.

[0027] In one embodiment, the compatibilizer is at least one of styrene, maleic anhydride grafted polyphenylene ether, epoxy resin, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted ethylene-propylene-butadiene, and maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer.

[0028] In one embodiment, the additive is an antioxidant and / or a lubricant;

[0029] The antioxidant is at least one of 2,4,6-tri-tert-butylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(nonylphenyl)phosphite or tris(2,4-di-tert-butylphenyl)phosphite;

[0030] The lubricant is at least one of N,N'-ethylenebisstearamide, octadecanoic acid, calcium stearate, stearate, and erucamide.

[0031] In the present application, the PPS composite material can have a better anti-oxidation effect by controlling the type of antioxidant, and the above-mentioned lubricant can achieve a better lubrication effect.

[0032] On the other hand, a method for preparing the PPS composite material is provided, comprising the following steps:

[0033] The components are mixed uniformly in proportion to obtain a mixture A; the mixture A is added to the main feeding port of a twin-screw extruder, and the glass fiber is added to the side feeding port of the twin-screw extruder, and the mixture is melt-extruded and granulated to obtain a PPS composite material.

[0034] Preferably, the temperature of the melt extrusion is 220-320°C.

[0035] On the other hand, the application of the PPS composite material in electronic appliances, electronic packaging, industrial equipment, and automotive electronics is provided, such as parts such as battery poles, high-temperature-resistant electronic trays, turnover boxes, wafer boxes, etc.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The present invention improves the resistance stability and dimensional stability of PPS composite materials while ensuring the mechanical properties of PPS composite materials by compounding PPS resins with different melt indexes, thereby avoiding the shortcomings of poor flow properties of low melt index materials and poor mechanical properties of high melt index materials.

[0038] 2. The present invention uses PPE resin as a dispersed phase to improve the fusion of each component and PPS resin, and further improve the resistance stability and dimensional stability of the PPS composite material.

[0039] 3. The present invention discloses that graphite and glass fiber are compounded for use. Graphite can reduce the anisotropy of glass fiber reinforced PPS, thereby reducing the difference in shrinkage between the perpendicular flow direction and the parallel flow direction, inhibiting the warping of the PPS composite material, and improving the dimensional stability of the PPS composite material.

[0040] 4. The present invention utilizes the interaction between graphite and carbon nanotubes to improve the resistance stability of the PPS composite material while further improving the dimensional stability. DETAILED DESCRIPTION

[0041] In order to better illustrate the purpose, technical scheme and advantages of the present disclosure, the present disclosure will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present disclosure in detail, rather than to limit the present disclosure. All other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure. The experimental reagents and instruments involved in the implementation of the present disclosure are all commonly used ordinary reagents and instruments unless otherwise specified.

[0042] The raw materials used in the embodiments and comparative examples are described below, as shown in Table 1, but are not limited to these materials:

[0043] Table 1

[0044]

[0045]

[0046]

[0047] Examples and Comparative Examples

[0048] The components and weight proportions of the PPS composite materials of the embodiment and the comparative example are shown in Table 2 and Table 3, wherein the additive is tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, tris[2,4-di-tert-butylphenyl]phosphite and pentaerythritol stearate lubricant compounded in a mass ratio of 0.1:0.2:0.7; the preparation method of the PPS composite materials of the embodiment and the comparative example comprises the following steps:

[0049] (1) Weigh various components according to the ratio;

[0050] (2) uniformly mixing the first PPS resin, the second PPS resin, the PPE resin, graphite, the carbon nanotubes, the compatibilizer and the additive to obtain a mixture A;

[0051] (3) Add the mixture A obtained in step (2) to the main feed port of a twin-screw extruder, add the glass fiber to the side feed port of the twin-screw extruder, the screw temperature of each section of the twin-screw extruder is 220-320° C., and melt-extrude and granulate to obtain a PPS composite material.

[0052] Table 2

[0053]

[0054]

[0055] Table 3

[0056]

[0057] Performance Testing

[0058] 1. Dimensional stability (warpage): Injection molded 60mm*60mm*1.0mm square plate, test the maximum warpage before and after baking, the baking condition is 120℃, 4h.

[0059] 2. Resistance stability: The sample was injection molded into a 360mm×100mm×3mm flat plate. According to ASTMD257:2014 standard, a VC9808 multimeter was used to test the resistance values ​​in the vertical and parallel directions. Resistance stability = parallel direction resistance value ÷ vertical direction resistance value × 100%.

[0060] The test results are shown in Table 4.

[0061] Table 4

[0062] Warpage before baking / mm Warpage after baking / mm Resistance stability / % Example 1 0.82 0.84 65.05 Example 2 0.95 1.04 35.07 Example 3 0.90 0.95 48.08 Example 4 0.93 1.00 46.08 Example 5 0.98 1.05 48.34 Example 6 0.97 1.03 61.2 Example 7 1.33 1.48 52.3 Example 8 1.18 1.2 42.74 Example 9 0.85 0.87 78.30 Example 10 0.99 1.03 42.86 Embodiment 11 0.95 0.98 57.47 Example 12 0.82 0.88 63.2 Example 13 1.02 1.04 39.09 Embodiment 14 1.18 1.22 59.06 Embodiment 15 0.80 0.85 60.33 Example 16 0.83 0.85 53.46 Embodiment 17 0.98 1.02 42.9 Embodiment 18 0.88 0.92 54.2 Comparative Example 1 1.08 1.11 27.29 Comparative Example 2 1.11 1.19 34.01 Comparative Example 3 1.25 1.33 6.18 Comparative Example 4 0.88 0.89 8.73

[0063] It can be seen from the test data in Table 3 that the PPS composite material prepared in the embodiment of the present disclosure has excellent dimensional stability and resistance stability.

[0064] From the comparison between Example 1 and Examples 3-4, it can be seen that when the viscosity of the PPE resin is in the range of 20-50 cm3 / g, the obtained PPS composite material has good dimensional stability and conductive stability; further, when the viscosity of the PPE resin is in the range of 20-30 cm3 / g, the obtained PPS composite material has better dimensional stability and conductive stability.

[0065] From the comparison between Example 1 and Example 5, it can be seen that compared with the glass fiber treated with a silane coupling agent, the PPS composite material prepared from the glass fiber treated with polyurethane has better comprehensive properties.

[0066] From the comparison between Example 1 and Examples 6-8, it can be seen that when the average particle size of graphite is 10-80 μm, the comprehensive performance of the obtained PPS composite material is better; when the average particle size of graphite is 25-50 μm, the comprehensive performance of the obtained PPS composite material is better.

[0067] From the comparison between Example 1 and Examples 9-10, it can be seen that when the ratio of the total mass of the first PPS resin and the second PPS resin to the mass of the PPE resin is (2:1)-(5:1), the comprehensive performance of the PPS composite material is better.

[0068] From the comparison between Example 1 and Examples 11-13, it can be seen that when the carbon nanotubes are 1-3 parts, the comprehensive performance of the obtained PPS composite material is better.

[0069] From the comparison between Example 1 and Examples 14-15, it can be seen that when the content of glass fiber is 25-35 parts, the comprehensive performance of the obtained PPS composite material is better.

[0070] From the comparison between Example 1 and Examples 16-17, it can be seen that when the content of graphite is 5-10 parts, the comprehensive performance of the obtained PPS composite material is better.

[0071] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present disclosure rather than to limit the protection scope of the present disclosure. Although the present disclosure has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present disclosure can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present disclosure.

Claims

1. A PPS composite material, characterized in that: The invention comprises the following components in parts by weight: 10-40 parts of a first PPS resin, 10-40 parts of a second PPS resin, 10-30 parts of a PPE resin, 10-40 parts of glass fiber, 5-15 parts of graphite, and 0.5-5 parts of carbon nanotubes; wherein the melt index of the first PPS resin at 316° C. and 5 kg is 200-500 g / 10 min; the melt index of the second PPS resin at 316° C. and 5 kg is 1000-2000 g / 10 min; The graphite is flake graphite, and the average particle size of the graphite is 10-80 μm; the average particle size of the graphite is tested by the following method: a 20 wt% aqueous solution of sodium hexamethylphosphate and a graphite sample are added to a 100 ml beaker, and then dispersed for 30 minutes using an ultrasonic disperser, and the solution is added to the chamber of a laser scattering particle size measuring machine MICROTRAC HRA Nikkiso Co., Ltd. 9320-X100, and the volume distribution is measured with a measuring time of 120 seconds, and the particle size of 50% of the measured volume distribution is taken as the average particle size.

2. The PPS composite material according to claim 1, characterized in that The average particle size of the graphite is 25-50 μm.

3. The PPS composite material according to claim 1, characterized in that The intrinsic viscosity of the PPE is 20-50 cm 3 / g; The viscosity of PPE is tested by the following method: weigh 0.250±0.002g of dry sample, transfer to a 50mL volumetric flask, add 15mL of chloroform, shake to completely dissolve the sample, then dilute to the scale with chloroform at 25°C, and shake well; before the measurement, filter the solution with a glass sand core funnel, and rinse the filter device and Ubbelohde viscometer with a small amount of solution, add the filtered solution to the Ubbelohde viscometer so that the liquid level is between the liquid filling marks; install the Ubbelohde viscometer in the constant temperature water bath of the Ubbelohde viscometer at 25.0±0.1°C, ensure that the viscosity tube is vertical, and the upper mark is at least 30mm below the water bath surface, and after constant temperature for 15 minutes, measure the flow time of the sample; The intrinsic viscosity of the PPE was calculated from the flow-through time.

4. The PPS composite material according to claim 3, characterized in that: The intrinsic viscosity of the PPE is 20-30 cm 3 / g.

5. The PPS composite material according to claim 1, characterized in that: The weight portion of the glass fiber is 25-35 parts; And / or, the glass fiber has a diameter of 10-15 μm, a length of 3-6 mm, and a surface treated with polyurethane; And / or, both the first PPS resin and the second PPS resin have linear structures.

6. The PPS composite material according to claim 1, characterized in that: The ratio of the total mass of the first PPS resin and the second PPS resin to the mass of the PPE resin is (2:1)-(5:1).

7. The PPS composite material according to claim 1, characterized in that: The PPS composite material further comprises 5-15 parts by weight of a compatibilizer and 1-3 parts by weight of an additive; The compatibilizer is at least one of maleic anhydride grafted polyphenylene ether, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted ethylene-propylene-butadiene, and maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer; The additive is an antioxidant and / or a lubricant.

8. The PPS composite material according to claim 7, characterized in that: The antioxidant is at least one of 2,4,6-tri-tert-butylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(nonylphenyl)phosphite or tris(2,4-di-tert-butylphenyl)phosphite; The lubricant is at least one of N,N'-ethylenebisstearamide, octadecanoic acid, stearate, and erucamide.

9. The PPS composite material according to claim 8, characterized in that: The stearate is calcium stearate.

10. A method for preparing a PPS composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The components are mixed uniformly in proportion to obtain a mixture A; the mixture A is added to the main feeding port of the screw extruder, and the glass fiber is added to the side feeding port of the screw extruder, and the PPS composite material is obtained by melt extrusion and granulation.

11. Application of the PPS composite material according to any one of claims 1 to 9 in automobiles, electric tools and household appliances.

Citation Information

Patent Citations

  • Polyphenylene sulfide composite material for high-filling low-warping battery module end plate, and preparation method thereof

    CN110776742A

  • Reinforced polyphenylene sulfide composite material with low floating fiber, low warping and high glass fiber content, and preparation method thereof

    CN112812562A

  • High-temperature anti-static polyphenyl ether composite engineering material and preparing method thereof

    CN102643528A

  • Antimicrobial low-warpage low-flash PPS composite material and preparation method thereof

    CN107189438A